2020
DOI: 10.3390/jrfm13060116
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrency Returns before and after the Introduction of Bitcoin Futures

Abstract: This paper examines the behaviour of Bitcoin returns and those of several other cryptocurrencies in the pre and post period of the introduction of the Bitcoin futures market. We use the principal component-guided sparse regression (PC-LASSO) model to analyze several sample sizes for the pre and post periods. Besides the neighbourhood of the break time, the current period is also investigated as returns start to recover after some time. Search intensity is observed to be the most important variable for Bitcoin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Lagged XRP returns, NYSE and the Mom introduced by Fama and French (1993), have positive effects on the current daily returns of the XRP. This finding coincides with Deniz and Stengos (2020), where a positive correlation between the XRP market and the NYSE index is also discovered.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Lagged XRP returns, NYSE and the Mom introduced by Fama and French (1993), have positive effects on the current daily returns of the XRP. This finding coincides with Deniz and Stengos (2020), where a positive correlation between the XRP market and the NYSE index is also discovered.…”
Section: Resultssupporting
confidence: 86%
“…In contrast, the lagged returns from S&P 500, Mom and Euro have negative effects. This finding is also consistent with Deniz and Stengos (2020). It suggests that the LTC market is contemporaneously positively correlated with the gold market, the Forex market, and the financial market's momentum while being negatively affected by the lagged information from the markets above.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In particular, they propose a shrinkage Mallows model averaging (SMMA) estimator for forecasting, and they find that the returns for most cryptocurrencies are sensitive to volatilities from major financial markets. Deniz and Stengos (2020), in "Cryptocurrency Returns before and after the Introduction of Bitcoin Futures", also examined the behaviour of Bitcoin returns and those of several other cryptocurrencies in the periods before and after the introduction of the Bitcoin futures market by using a principal-component-guided sparse regression (PC-LASSO) model to analyze several sample sizes for the before and after periods, and they found that the top-five cryptocurrencies were substitutes before the launch of Bitcoin futures. However, this effect was lost, and moreover, there were spillover effects on altcoins during both the after and the recovery periods.…”
mentioning
confidence: 99%